2020
DOI: 10.1108/ijph-07-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Mental health interventions in an Italian prison: the Parma integrated approach

Abstract: Purpose Mental health interventions for Italian prisoners with mental disorders remain a problematic issue, despite radical changes in general psychiatric care and a 2008 major government reform transferring mental health care in prison to the National Health Service. The aim of this study is to describe the mental health intervention model implemented since January 2020 for prisoners allocated in the Parma Penitentiary Institutes (PPI). This approach is specifically based on specialized, “person-centered” and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This has necessitated several measures from governmental bodies and other stakeholders to reduce the rate at which the virus was invading prisons and correctional centers both in the USA and around the globe. In Italy, stringent measures were put in place to prevent intrusion of the outside community into prisons and correctional facilities (Cingolani et al, 2020;Pelizza et al, 2020). The same was the case in China, Nigeria, Brazil, Ghana and the USA (Franco-Paredes et al, 2020;Ofori et al, 2020).…”
mentioning
confidence: 99%
“…This has necessitated several measures from governmental bodies and other stakeholders to reduce the rate at which the virus was invading prisons and correctional centers both in the USA and around the globe. In Italy, stringent measures were put in place to prevent intrusion of the outside community into prisons and correctional facilities (Cingolani et al, 2020;Pelizza et al, 2020). The same was the case in China, Nigeria, Brazil, Ghana and the USA (Franco-Paredes et al, 2020;Ofori et al, 2020).…”
mentioning
confidence: 99%
“…The PPI is not a special kind of mental health prison and inmates are not selectively placed due to them having specific mental health care needs (for details, see Pelizza et al 3 ). Prisoners are assigned to the PPI simply based on their geographical location or because they have committed specific kind of serious criminal offenses.…”
Section: Methodsmentioning
confidence: 99%
“…1 Specifically, results of recent epidemiological research in Italy suggested that although 70% to 75% of Italian inmates show some kind of psychiatric disorders, severe mental illness (most of them generically defined as "psychosis") represents approximately 4% to 5% of the total cases. 2,3 Substance use disorder is also a major disabling diagnosis in Italian prisoners. 4 In this respect, it has been reported that more than 35% of the Italian inmates has pathological substance dependence already before the prison admission.…”
mentioning
confidence: 99%
“…Italy, mental health, outcomes, prison, psychological screening, suicide risk as to ensure the continuity of care during their 'intramural-extramural' transition (Pelizza, Zaimovic, et al, 2021) and (3) structuring according to different prison-time phases: reception, detention and release from prison. The reception phase includes a specific psychological service for newly admitted inmates consisting of a clinical interview by a clinical psychologist to assess suicide risk and adjustment reaction to prison and to detect current mental disorder, drug abuse and severe psychological distress (Pelizza, Zambelli, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the Italian government decided to transfer responsibility and resources for mental health care in prison from the Ministry of Justice to the National Health System, to be organised and funded regionally (La Cerra et al., 2017). On this background and according to a recent resolution of the Regional Council of the Emilia‐Romagna Region (resolution n. 2051/2019 entitled ‘Regional health programme in prisons’) (Regione Emilia Romagna [RER], 2019a), the Parma Department of Mental Health implemented an integrated mental health intervention model for prisoners in the local prisons, modelled on the community‐based treatment approach usually provided in Italian adult mental healthcare services (Pelizza, Zambelli, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%